Co-infection and emergence of rifamycin resistance during a recurrent Clostridium difficile infection - Stevenson, Emma C.; Major, Giles A.; Spiller, Robin C.; Kuehne, Sarah A.; Minton, Nigel P. (American Society for Microbiology, 2016)
Clostridium difficile (Peptoclostridium difficile) is a common health care-associated infection with a disproportionately high incidence in elderly patients. Disease symptoms range from mild diarrhea to life-threatening pseudomembranous colitis. Around 20% of patients may suffer recurrent disease, which often requires rehospitalization of patients. C. difficile was isolated from stool samples from a patient with two recurrent C. difficile infections. PCR ribotyping, whole-genome sequencing, and phenotypic assays were used to characterize these isolates. Genotypic and phenotypic screening of C. difficile isolates revealed multiple PCR ribotypes present and the emergence of rifamycin resistance during the infection cycle. Understanding both the clinical and bacterial factors that contribute to the course of recurrent infection could inform strategies to reduce recurrence. (This study has been registered at ClinicalTrials.gov under registration no. NCT01670149.)